Instructional Methods for Teaching Social Studies: A Survey of What Primary School Children Like and Dislike about Social Studies Instruction - Shah, Rajendra Kumar (Journal of Tikapur Multiple Campus, 2014)
Sufficient research studies are not conducted in the field of primary level social studies curriculum pertaining to effective instructional pedagogy. At the same time, research studies conducted in the field of primary level social studies fail to take into account one very important variable: How do the primary school children enjoy learning social studies? This paper is a survey research study designed to see what a group of primary school children liked and disliked about social studies instruction. By asking the questions the researcher hope to gain a better understanding of primary school children' preferences, attitudes and perceptions of social studies instruction. The major objective of this study is to gain a better understanding of what instructional methods the students enjoy in the social studies classroom. The findings of this study will be help for teacher in selection of proper teaching learning strategies.